Avoiding Middle-Income Growth Traps - Agénor, Pierre-Richard; Canuto, Otaviano; Jelenic, Michael (2014)
Since the 1950s, rapid growth has allowed a significant number of countries to reach middle-income status; yet, very few have made the additional leap needed to become high-income economies. Rather, many developing countries have become caught in what has been called a middle-income trap, characterized by a sharp deceleration in growth and in the pace of productivity increases. Drawing on the findings of a recently released working paper (Agenor and Canuto 2012), as well as a growing body of research on growth slowdowns, this note provides an analytical characterization of 'middle-income traps' as stable, low-growth economic equilibrium where talent is misallocated and innovation stagnates. To counteract middle-income traps, there are a number of public policies that governments can pursue, such as improving access to advanced infrastructure, enhancing the protection of property rights, and reforming labor markets to reduce rigidities all implemented within a context where technological learning and research and development (R&D) are central to enhancing innovation. Such policies not only explain why some economies particularly in East Asia were able to avoid the middle-income trap, but are also instructive for other developing countries seeking to move up the income ladder and reach high-income status.